Employed Bacterial Species and Bacterial Cellulose (BC) Applications: The State of Play - Wan Syahiidah Wan Abd Aziz; Azila Adnan (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2022)
Bacterial cellulose (BC) is an uprising bio-polymer produced by various bacterial strains, which is infamous for its prominent biological properties and applications. Receiving ample attention due to those unique properties, various genus and bacterial strains have been used for BC biosynthesis and the studies of its production have been recorded throughout the years. Although a lot of research and implementation has been done on BC, studies in the search for low-cost, effective medium contributing to higher BC yields were still in continuation to this day. This review article overviews the employed bacterial strains and their recent advance, modified, and low-cost medium in the development of BC composites. Special emphasis is placed on the new-novel strains for BC production and BC applications. Compilations of literature were compiled to outline the sources and also findings by previous and recent researchers. It was found that numerous studies have attempted to enhance BC production, which includes the utilization of various bacterial strains to fulfill industrial needs. Hence, this review comprises bacterial genera and species, which are mainly used in the production of BC such as Komagataeibacter, Gluconobacter, Gluconacetobacter, Enterobacter, and Pseudomonas.The recent studies enforced on BC focusing on higher production and the application of BC on an industrial scale will also be reviewed.